Effective Training: Synergy of Instructor Competence, Training Facilities and Participant Satisfaction with Performance - Hafrizal, Irham; Maliki, Budi Ilham; Komarudin, Mamay (Jurnal Economic Resource, 2025)
Improving the quality of human resources (HR) is a crucial strategy in facing the era of Industry 4.0. The Job Training Unit (UPTD) of the Cilegon City Manpower Office plays a role in preparing a competent workforce, but still faces obstacles such as limited facilities, suboptimal instructor competency, and low participant satisfaction. The aim of this study is to analyze the influence of instructor competence and training facilities on participant performance, with participant satisfaction as a mediating variable. This study used a quantitative approach with an explanatory design. A sample of 100 participants was determined using the method of Hair et al., data were collected using a Likert-scale questionnaire, and analyzed using PLS-SEM. The research results show that instructor competence and training facilities have a positive and significant impact on participant satisfaction. Satisfaction has been shown to improve performance and mediate the relationship between the variables. In conclusion, improving instructors and facilities is key to increasing participant satisfaction and performance, while strengthening human capital theory and providing practical implications for job training management.